The occurrence and probabilistic risk of exposure to parabens from bottled and hand-shaken teas in the general adult population of Taiwan - Chin, Wei-Shan; Chang, Chia-Huang; Say, Yee How*; Chuang, Yung-Ning; Wang, Jui-Ning; Kao, Ho-Ching; Liao, Kai-Wei (Springer, 2024)
Parabens (PBs) are esters of p-hydroxybenzoic acid, and there are growing concerns due to their potential to disrupt endocrine function and their wide use as preservatives in foodstuffs, including beverages. The consumption of bottled and hand-shaken teas is gradually replacing traditional tea consumption through brewing. However, no study has reported PB concentrations in different types of teas or packaging and their associated health risks. Our aim was to determine the concentration of PBs (methyl- (MetPB), ethyl- (EthPB), propyl- (PropPB), butyl-paraben (ButPB)) in green, black, and oolong teas in two varieties of products (bottled and hand-shaken teas), using UPLC-MS/MS. Additionally, we estimated the health risks associated with tea consumption in the general adult population of Taiwan. A Monte Carlo simulation was applied to estimate the distribution of daily PB intake through bottled (n = 79) and hand-shaken (n = 71) tea consumption. Our findings revealed geometric mean concentrations in bottled green/black/oolong teas were 714.1/631.2/532.1 ng/L for MetPB, 95.2/ 30.5/14.9 ng/L for EthPB, 77.9/28.3/non-detected (ND) ng/L for PropPB, and 69.3/26.6/ND ng/L for ButPB. Hand-shaken green/black/oolong teas exhibited concentrations of 867.5/2258/1307 ng/L for MetPB, 28.5/28.8/14.5 ng/L for EthPB, 25.4/18.3/17.8 ng/L for PropPB, and 30.3/18.0/15.5 ng/L for ButPB. The median MetPB concentrations in hand-shaken black (2333 ng/L) and oolong teas (1215 ng/L) were significantly higher than those in bottled black (595.4 ng/L) and oolong teas (489.3 ng/L). Conversely, median concentrations of EthPB, PropPB, and ButPB in bottled teas were significantly higher than those in hand-shaken teas. MetPB was the predominant PB, constituting 73.2–91.9% in bottled teas and 85–94% in hand-shaken teas. Our results showed no health risks associated with bottled or hand-shaken tea consumption based on reference doses. However, the study highlights the importance of continued vigilance given the potential chronic exposure to PBs from various sources, necessitating ongoing concern despite the absence of immediate risks from tea consumption.